Uncomplicated Diverticular Disease: Innate and Adaptive Immunity in Human Gut Mucosa before and after Rifaximin - Rossella Cianci; Simona Frosali; Danilo Pagliari; Paola Cesaro; Lucio Petruzziello; Fabio Casciano; Raffaele Landolfi; Guido Costamagna; Franco Pandolfi (Journal of Immunology Research, 2014)
Background/Aim. Uncomplicated diverticular disease (UDD) is a frequent condition in adults. The pathogenesis of symptoms remains unknown. Bacteria are able to interact with Toll-like receptors (TLRs) and to induce inflammation through both innate immunity and T-cell recruitment. We investigated the pattern of TLRs 2 and 4 and the intestinal homing in patients with UDD before and after a course of Rifaximin. Methods. Forty consecutive patients with UDD and 20 healthy asymptomatic subjects were enrolled. Among UDD patients, 20 were assigned to a 2-month course of treatment with Rifaximin 1.2 g/day for 15 days/month and 20 received placebo. Blood sample and colonic biopsies were obtained from patients and controls. The samples were collected and analyzed at baseline and at the end of treatment. Flow cytometry was performed using monoclonal antibodies (CD3, CD4, CD8, CD103, TCR-gamma/delta, CD14, TLR2, and TLR4). Results. In UDD, TLR2 and TLR4 expression on immune cell subpopulations from blood and mucosa of the affected colon are altered as compared with controls. Rifaximin treatment induced significant modifications of altered conditions. Conclusions. Our data show the role of TLRs in the development of inflammation in UDD. TLRs distribution is altered in UDD and these alterations are reversed after antibiotic treatment. This trial is registered with ClinicalTrials.gov: NCT02068482.